Cell Generator: A Self‐Sustaining Biohybrid System Based on Energy Harvesting from Engineered Cardiac Microtissues. (21st March 2017) - Xu, Bingzhe; Lin, Xudong; Li, Wei; Wang, Zixun; Zhang, Wenchong; Shi, Peng
Abstract : Biohybrid soft robotic devices present unique advantages for designing biologically active machines that can dynamically sense and interact with complex bioelectrical signals. Here, a controllable cell‐based machine is developed that harvests energy from arrays of beating cardiomyocytes to generate electricity for biomedical microscale robotic applications. The "Cell Generator" device is based on an array of piezoelectric microcantilevers wrapped with 3D patterned cardiac cells. Spontaneous contraction of the engineered cardiac constructs provides the source of mechanical energy for electricity generation. It is demonstrated that a single "Cell Generator" unit with 40 cantilevers can output peak voltages of ≈70 mV, and a larger array of 540 cantilevers can directly generate a pulsed output as high as ≈1 V. When integrated with an electrical rectification and storage circuit, it is further shown that the "Cell Generator" can provide functional outputs and work as a self‐powered neural stimulator to evoke action potentials in cultured neuronal networks. This demonstration of "Cell Generator" technology provides an innovative perspective of exploiting live biological powering system on biomedical microscale robotic devices in the human body. Abstract : A biohybrid system—"Cell Generator"— is fabricated by patterning cardiomyocytes on arrays of microcantilevers made of piezoelectric materials. Pulsed contraction of the engineered cardiac constructs provides the source of mechanical energy for electricity generation, which is used to power biomedical devices. This technology provides an innovative perspective of exploiting live biological components for the development of self‐sustaining cellular machines.